2020
DOI: 10.1007/s10798-020-09627-5
|View full text |Cite
|
Sign up to set email alerts
|

Short and long term impact of a high-tech STEM intervention on pupils’ attitudes towards technology

Abstract: The immediate and retention effects of a high-tech learning intervention on pupils' attitudes towards technologyAbstract STEM presents a challenge to education at large. The enrollment numbers in higher education STEM tracks are ever-decreasing numbers all around the globe. More so, young people's interest in and attitudes towards STEM seem to be free falling. Educational interventions that can help boost the attractiveness of STEM are therefore needed, and diverse such interventions are implemented worldwide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…[47,81,131,133,151] Behavior Collaboration • Providing supplemental hands-on training sessions. [17] Behavior Competence • Motivate teachers, in particular those teaching nonacademic tracks. [142] Behavior Confidence • Improved confidence through the use of geospatial technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47,81,131,133,151] Behavior Collaboration • Providing supplemental hands-on training sessions. [17] Behavior Competence • Motivate teachers, in particular those teaching nonacademic tracks. [142] Behavior Confidence • Improved confidence through the use of geospatial technologies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 65,161,173] Interest • Early exposure to meaningful experiences and encourage an out-of-school program that engages authentic STEM experiences. [17,55,151] Self-concept • Disentangle instrumental and expressive aspects of gender inequality in STEM fields. [60] Note: [ 90,91,135] Parental involvement • Encourage the importance of discouraging the use of stereotypes about careers among young children.…”
Section: Confidencementioning
confidence: 99%
“…Boeve-De Pauw and colleagues (2020) also found that even a one-day intervention (visiting technology and science workshops) can have a positive impact on girls' interest in a STEM career. By focusing more on design and technology workshops and making them more accessible to girls by letting them develop their own design, opportunities can be created to make the hard sciences more attractive (Ardies et al, 2015b;Boeve-De Pauw et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, local higher education system occupies a certain proportion of the limited local resources such as labor resources, financial resources, land resources, etc., which squeezes the resources of science popularization and hinders the growth of science popularization [ 24 ]. What is more, some elements of higher education may hinder the attractiveness of science popularization activities; for instance, some academic research articles written by university faculties are unintelligible and obscure, which decreases the enthusiasm of public to science and technology, reduces the effects of science popularization activities, and increases the difficulty of science popularization work [ 10 , 25 ]. Besides, it is found that improper planning or tactics of higher education development decreases the effectiveness and successfulness of science popularization, thus higher education institutions should make use of science popularization activities wisely and properly [ 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%